2019
DOI: 10.1183/13993003.00081-2018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of patients with systemic lupus erythematosus-associated pulmonary arterial hypertension: CSTAR-PAH cohort study

Abstract: This study aimed to identify the long-term clinical outcomes and prognostic factors of patients with systemic lupus erythematosus (SLE)-associated pulmonary arterial hypertension (PAH) confirmed by right heart catheterisation.A multicentre prospective cohort of SLE-associated PAH was established. Baseline and follow-up records were collected. The primary end-point was death. The secondary exploratory end-point was treatment goal achievement (TGA), defined as an integrated outcome.In total, 310 patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 32 publications
3
72
0
Order By: Relevance
“…A T2T strategy in SLE, which asserted that complete remission is the main target of SLE therapy, has been recommended by an international task force . Qian et al had already reported that treatment goal achievement (TGA) was associated with long‐term survival, which supports the T2T strategy in SLE‐associated PAH. However, challenges are met in the subgroup with pSS‐PAH.…”
Section: Discussionmentioning
confidence: 99%
“…A T2T strategy in SLE, which asserted that complete remission is the main target of SLE therapy, has been recommended by an international task force . Qian et al had already reported that treatment goal achievement (TGA) was associated with long‐term survival, which supports the T2T strategy in SLE‐associated PAH. However, challenges are met in the subgroup with pSS‐PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been a number of survival studies of SLE in the past decade, not too many were performed in the Asian populations (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Analysis of the survival of hospitalized patients (9,22), those admitted to the intensive care unit (12,19) or referred to tertiary centers (23), subsets of patients with nephritis (14), neuropsychiatric manifestations (17), or pulmonary hypertension (15) in some studies would create bias in the mortality rate. Moreover, the follow-up of most of these Asian studies was not long enough to look at the trend of survival over time.…”
Section: Introductionmentioning
confidence: 99%
“…All of the selected patients fulfilled the following inclusion criteria: ‹ age !18 years; › intensive immunosuppressive therapy initiated at our hospital; and fi regular follow-up. Intensive immunosuppressive therapy was defined as therapy with glucocorticoids and immunosuppressants [18]. Regular follow-up means that patients visited specialist physicians regularly every 1-3 months.…”
Section: Methodsmentioning
confidence: 99%